Missed Appointments and Associated Factors Among Children Accessing Anti-Retroviral Therapy During the COVID-19 Pandemic in South Western Uganda - Nduhukire T; Adebayo IA; Luwaga R; Mandela I; Napyo A; Ainamani H; Musiime V (HIV/AIDS: Research and Palliative Care, 2025)
Timothy Nduhukire,1 Ismail Abiola Adebayo,2 Rachel Luwaga,3 Immaculate Mandela,4 Agnes Napyo,4 Herbert Ainamani,5 Victor Musiime6 1Department of Pediatrics and Child Health, Kabale University School of Medicine, Kabale, Uganda; 2Department of Microbiology, Kabale University School of Medicine, Kabale, Uganda; 3Department of Nursing Science, Mbarara University of Science and Technology, Mbarara, Uganda; 4Department of Nursing, Kabale University School of Medicine, Kabale, Uganda; 5Department of Mental Health, Kabale University School of Medicine, Kabale, Uganda; 6Department of Pediatrics and Child Health, Makerere University College of Health Science, Kampala, UgandaCorrespondence: Timothy Nduhukire, Email timnduhukire@kab.ac.ugBackground: Disruptions to the health sector in Uganda during the COVID 19 pandemic affected health services in the early phases of the pandemic. Not much data exists on their effect on these same services during the later stages of the pandemic especially for children. To fill this gap, we set out to study missed appointments and their associated factors during the lockdown for children receiving Anti-Retroviral Therapy (ART).Methods: This was a retrospective cohort study from January 2022 to May 2022. We included all children aged 0– 15 and adolescents aged 15– 19 years who were on ART. Electronic Medical Records (EMR) for the participants in the last 12 months were extracted. Descriptive statistics are presented. Binary logistic regression was performed, and odds ratios were reported.Results: Out of the 382 participants, 26 (6.8%) missed appointments during the study period. The likelihood of missing appointments was increased when drugs were given to last 4 months than when they were given to last one month (COR 3.207, P value 0.026, 95% CI 1.150– 8.943). Patients were also more likely to miss appointments if their mode of receiving drugs was Facility based group (COR 3.174, P = 0.043, 95% CI 1.037– 9.713). Not having a viral load in the last 12 months increased the likelihood of missing an appointment (COR 2.309, P = 0.049, CI 1.004– 5.306).Conclusion: A drug refill of 4 months and being scheduled to receive drugs by Facility-based group model predisposed the participants to missing the next appointment. Home- or community-based ART delivery to clients as well as drug prescriptions for a longer period could reduce missed appointments. Timely viral load testing should be encouraged as it correlates with adherence to appointments. More research is needed on the safety, storage practices and efficacy of ART given to last more than 2 months.Keywords: COVID 19, pandemic, anti-retroviral therapy, missed appointments, electronic medical records viral load